Evaluation of Creatinine Levels, Ureum Levels, Urine Protein in Diabetes Mellitus Patient as a Predictor of Kidney Failure - Ika Nurfajri Mentari; Tri Utari Agustina; Jumari Ustiawaty; Pauzan Pauzan (Yayasan Ahmad Mansyur Nasirah, 2026)
Chronic kidney failure is a common microvascular complication of diabetes mellitus, and kidney function is routinely evaluated using creatinine, urea, and urinary protein tests. However, because creatinine and urea testing requires automated laboratory equipment that is often unavailable in primary healthcare facilities, urinary protein testing remains the most accessible screening method for the early detection of kidney function impairment. The purpose of this study is to evaluate creatinine levels, urea levels, and urine protein in patients with Diabetes Mellitus as predictors of kidney failure. This study is a quantitative descriptive study with a cross-sectional approach. The independent variables are creatinine levels, urea levels, and urine protein, while the dependent variable is blood glucose levels. The study sample consisted of 30 individuals using accidental sampling technique. Data collection was conducted using secondary data. The data were analyzed descriptively and with the Pearson chi-square test. The research results showed that 47% of respondents had high creatinine levels, 83% had high urea levels, and 80% had positive urine protein results, including positive levels 1, 2, and 3. The Pearson chi-square test results indicated that all three variables creatinine, urea, and urine protein had a significant relationship with p-values less than 0.05, specifically creatinine at 0.045, urea at 0.037, and urine protein at 0.032. The conclusion that can be drawn from these results is that the examination of creatinine levels, urea levels, and urine protein can serve as predictors of kidney failure in patients with diabetes mellitus. In particular, urine protein levels can be a simple test used to detect kidney conditions in diabetes mellitus patients and can be performed at community health centers.